Ion beam dynamics of a 3 kilo joule plasma focus using Lee's model - Nina Diana Nawi, 1989-, author; Jalil Ali, 1959-, supervisor; Fakulti Sains (2015)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2015